Flow processes in faults and shear zones - Alsop, G. I. (Geological Society special publication ;, 2004)
Alsop et al. compile 22 papers, most of which were presented at the joint international meeting of the Tectonic Studies Group of the Geological Society, London, the Structural Geology and Tectonics Division of the Geological Society of America, and the Geological Society of Australia in September of 2002. They discuss and analyze aspects of faults.